2014
DOI: 10.1108/nfs-10-2013-0115
|View full text |Cite
|
Sign up to set email alerts
|

Legumin from chickpea: hypolipidemic effect in the liver of hypercholesterolemic rats

Abstract: Purpose – This paper aims to determine the effects of 11S globulin isolated from Chickpea (Cicer arietinum L.) on lipid metabolism in animals subjected to a hypercholesterolemic and hyperlipidemic diet and compared to the drug simvastatin. Design/methodology/approach – Thirty-six male Wistar rats, kept in individual cages and under appropriate conditions, were separated into groups that were fed a normal diet (STD) containing casein as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The appearance of two 7S globulin bands of about 28 and 52 kDa corresponds to the basic and acidic subunits and such results concur with other published work in this respect. Also, the molecular mass study of 7S globulin showed bands of about 132, 129 and 95 kDa and those bands correspond to α’, α and β subunits and those showed that such globulin protein is similar to that of chickpea [36]; SDS-PAGE of chickpea legumin exhibited five bands corresponding to smaller molecular weights of about 25–45 kDa in accordance with previous results in this respect which reported a molecular weight range of about 18-41 kDa for these subunits. The variations in the minimal molecular weight may be due to different plant varieties [31].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of two 7S globulin bands of about 28 and 52 kDa corresponds to the basic and acidic subunits and such results concur with other published work in this respect. Also, the molecular mass study of 7S globulin showed bands of about 132, 129 and 95 kDa and those bands correspond to α’, α and β subunits and those showed that such globulin protein is similar to that of chickpea [36]; SDS-PAGE of chickpea legumin exhibited five bands corresponding to smaller molecular weights of about 25–45 kDa in accordance with previous results in this respect which reported a molecular weight range of about 18-41 kDa for these subunits. The variations in the minimal molecular weight may be due to different plant varieties [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our protocol can be adopted for large-scale protein analyses in nutritional [ 14 , 18 , 22 ] and nutraceutical applicative fields [ 21 ], which may require animal or human testing [ 5 , 28 ], or for direct exploitation in specific formulation for human food [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, health-promoting biological activities have been associated with several proteins from legume seeds, primarily soybean [ 11 , 12 , 13 ], chickpea [ 14 , 15 ], lupin [ 16 ], cowpea [ 5 , 17 ], adzuki [ 5 ], and mung [ 18 ] beans. Peptides of different sizes have been shown to exert various beneficial effects, including anticancer, antimicrobial, antioxidant, antihypertensive, cholesterol-lowering, immunomodulatory actions as well as obesity and Type 2 diabetes prevention [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 7S and 11S globulins of different species of legumes affect lipid metabolism in vivo and in vitro (Amaral et al , 2014; Duranti, 2006; Ferreira et al , 2015; Pak et al , 2005). The amino acids sequences of the polypeptide chains and their potential structural interaction are conserved (Argos et al , 1985).…”
Section: Resultsmentioning
confidence: 99%